Challenges and opportunities for a CAMPEP-accredited Medical Physics Graduate Program in Galway, Ireland. (June 2019) - Kleefeld, C; Alaswad, M; Foley, M
Abstract: Established in 2002, this long running MSc in Medical Physics program was awarded CAMPEP accreditation in 2015, thus being one out of only two CAMPEP approved graduate programs outside North America. The program is a full-time, one-year taught master course delivered by a close university–hospital collaboration. This paper will give an outline of the current program structure and will identify challenges likely affecting the areas of teaching, research and course administration. Strategies to address these challenges will be discussed. Since the accreditation, the number of students enrolled in the program increased from 8 in 2015/16 and 16 in 2016/17 to 21 in 2017/18 and 25 in 2018/19. The number of non-EU students in these cohorts was 2, 5, 4, and 9 respectively. Non-EU students predominantly originate from North America and Saudi-Arabia. The total number of applicants averages at approximately 55 per year. A further increase in student intake has been advocated but might impact negatively on the quality of the clinical training which forms a vital part of the program. Students are given access to clinical systems for laboratory exercises as well as for pursuing research projects, thus gaining some clinical experience which will increase their employability. However, local clinical access has to be limited. In order to mitigate the situation, the program cooperates with medical physics departments nationwide and internationally. Curricular challenges arising from clinical implementations of ever-evolving technologies and from a rapidly changing medical physics landscape in general will be expanded on.